The Malay language and ethnic identity in modern Malaysia - Collins, James T.; Zaharani Ahmad (Universiti Kebangsaan Malaysia, 1999)
Colonial discourse about the Malay language and the Malay ethnic group were often at odds with each other. Yet, this conflicting, orientalistic mythology about “Malay” still functions in contemporary discussions about language and ethnicity in Malaysia. This essay aims at constructing a new vantage point from which to view Malay. Instead of focusing on its uniqueness, Malay is seen within the context of its language neighbourhood, that is its relationship to Malaysia’s other Malayo-Polynesian languages, Malaysia’s non-Malayo-Polynesian languages and the diverse regional and social dialects of Malay in Malaysia. Instead of discussing Malay as a political, nation-state phenomenon, Malay is considered as a demographic, emblematic and negotiated phenomenon. We must find new ways of looking at and talking about Malay language and Malay ethnicity; we need to produce new knowledge, not merely repeat colonial myths.